Relational Sociology Paradigms - Manterys, Aleksander (Stan Rzeczy, 2017)
This article is an analysis of three original variants of relational sociology. Jan A. Fuhse’s conception, which is part of the tradition of social network research, situates network analyses in the context of connections between culture and symbolic forms and styles. Fuhse’s idea involves a communicative base of relations, and he perceives institutions as spheres of communication that reduce uncertainty and activate roles in the process of communication. François Dépelteau’s approach, which is inspired by Dewey’s pragmatism, recognizes transaction fields as configurations of relations forming interdependency between people. The practices of actors entering transactions within social fields are important, and this makes it possible for an impression of continuity, order, and complexity to be created. Pierpaolo Donati’s relational realism is an attempt to describe the relational dimensions of human actions, while at the same time it is a consistent “relationization” of key social categories, and is also useful in understanding after-modernity. This article emphasizes the fruitfulness of new attempts to demarcate sociological genealogies and to read the classics of relational sociology. The author discusses the creation of new puzzles for sociological theory, the necessity of analysing the ontologies of social life, the phenomena of emergency and agency, and the use of relational theory in regard to categories of the common good and social capital. He encourages multidimensional and multilevel analyses of social reality.